Penerapan Enterprise Resource Planning Menggunakan Oddo pada Sistem Informasi Pembelian dan Penjualan Makanan Studi Kasus Angkringan Mamayo - Nauval Ramfa; Lufty Abdillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
At mamayo angkringan, the business processes of buying, inventorying, and selling food are still done manually. This causes several problems, among others, frequent errors in recording purchases and sales of goods, long transaction calculations, and slow information on the availability of goods in inventory. Therefore, it is necessary to implement Enterprise Resource Planning (ERP) and use ASAP as a research method. The selection of the right methodology helps companies to implement the system properly according to the criteria required by the company. The ASAP (Accelerated SAP) methodology can describe all activities in implementation, including all technical areas to support project management. The results of this study indicate that the ERP software that has been selected and implemented, namely the Odoo application, can overcome problems in the mamayo angkringan.